Current landscape of clinical use of ex vivo expanded natural killer cells for cancer therapy - Júlia Teixeira Cottas de Azevedo; Juliana Aparecida Preto de Godoy; Cláudia de Souza; Micheli Severo Sielski; Larissa Leggieri Coa; Augusto Barbosa Júnior; Lucila Nassif Kerbauy; Andrea Tiemi Kondo; Oswaldo Keith Okamoto; Nelson Hamerschlak; José Mauro Kutner; Raquel de Melo Alves Paiva (Einstein (São Paulo))
ABSTRACT Natural Killer cells are immune leukocytes required for responses against tumor cells and virus-infected cells. In the last decade, natural killer cells have emerged as promising tools in cancer therapy, and clinical studies on patients treated with natural killer cells have revealed increased rates of disease-free survival. In this article, we review results from the major clinical trials that have used natural killer cells for cancer treatment, including their global distribution. We also discuss the major mechanisms of natural killer cell activation and expansion and focus on the advantages and disadvantages of each mechanism for clinical applications. Although natural killer cells can be isolated from several sources, primary natural killer cells are most commonly used in clinical trials. However, the frequency of natural killer cells available in peripheral and cord blood is low, necessitating development of methods for expansion of natural killer cells for clinical use. The development of a platform for the expansion of large-scale good manufacturing practice-compliant natural killer cells has limitations as several methods for natural killer cell activation and expansion yield conflicting results. Only techniques using feeder cells can produce large numbers of cells, allowing the “off-the-shelf” use of natural killer cells. However, advances in cell culture have supported the development of feeder-free platforms for natural killer cell expansion, which is fundamental for improving the safety of this type of cell therapy.